Предмет: Математика,
автор: Сэр2003
7(4х-1)=6-2(3-14х)
5/6х+16=4/9х=9
4(х-1)=2(2х-8)=12
Ответы
Автор ответа:
0
У меня получилось так)
Приложения:
Автор ответа:
0
спасибо
Автор ответа:
0
5/6х+16=4/9х=9
4(х-1)=2(2х-8)=12
4(х-1)=2(2х-8)=12
Автор ответа:
0
сможешь помочь ПЖ
Автор ответа:
0
ок
Автор ответа:
0
а в первом уравнении там перед 9 равно ?
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Литература,
автор: timurivanuskin406
Предмет: История,
автор: Аноним
Предмет: Экономика,
автор: omnomnom133669